UPAYA MENINGKATKAN PENGETAHUAN DENGAN PEMBERIAN EDUKASI TENTANG FLATFOOT PADA SISWA SDN TULUSREJO 4: EFFORTS TO INCREASE KNOWLEDGE BY PROVIDING EDUCATION ABOUT FLAT FOOT TO STUDENTS OF SDN TULUSREJO 4 - Diah Nur Pratiwi; Sri Sunaringsih Ika Wardojo; Bonita Suharto (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Childhood is a very important period to pay attention to growth and development. Flatfoot is a condition where there is weakness in the supporting structure of the longitudinal arch or the entire sole of the foot in contact with the ground. The main cause of flatfoot is an abnormality in the bone structure so that this condition causes the muscles, tendons and ligaments to work harder. Although most cases of flatfoot occur in the form of physiological, but if the condition progresses to a worse stage, it can cause symptoms and affect the function of the sufferer's feet. In Indonesia, there are 27,574,728 elementary school students aged 7 to 12 years who experience flat feet. According to data, 30% of cases in urban areas are Flatfoot. The aim of this outreach in the children and youth community is to provide knowledge by means of flatfoot education to grade 5 students at SDN Tulusrejo 4, Malang City. Education in this activity is carried out to prevent permanent growth and development abnormalities. The method used in this activity uses counseling by providing leaflets and asking several pretest and posttest questions to find out the picture of students' knowledge about flatfoot. In this extension activity, students were enthusiastic about asking questions so that it became a factor in increasing students' knowledge. It can be concluded that physiotherapy counseling activities related to flatfoot for students at SDN Tulusrejo 4, Malang City, can run smoothly and are well realized and from the evaluation results it is found that there is an increase in knowledge and understanding of students at SDN Tulusrejo 4 regarding flatfoot with a post-test score of 100%.